Pemberdayaan Masyarakat melalui Program Pendidikan Kecakapan Wirausaha (PKW) Spa Therapist di LKP Berlian Education Training College Lombok Tengah - Rahman, Lalu Isnaeni; Hijriati, Sartika (Lembaga Yasin AlSys, 2022)
Central Lombok Regency is one of the regencies in NTB Province which is included in the category of underdeveloped areas. Many community empowerment programs are carried out for individuals and groups through empowerment programs according to community needs. Many programs run by the government require a pattern of partnerships with non-government parties carried out by non-formal educational institutions. The Entrepreneurial Skills Education Program (PKW) is an educational service for courses and training to provide knowledge, skills, and foster an entrepreneurial mental attitude in managing self-potential and the environment that can be used as provisions for entrepreneurship. LKP Berlian Eduacation Training College is a part of non-formal education that is very active and plays a role in providing knowledge of entrepreneurship skills and attitudes for the people of Central Lombok.